(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: A duct-to-mucosa pancreatojejunostomy is technically difficult to perform than Dunking procedure after pancreatoduodenectomy. In contrast, the incidence of anastomotic dehiscence is more in Dunking than duct-to-mucosa procedure. Duct-to-mucosa technique is rarely practiced in our country because of technical difficulties and lack of experiences. Objectives: This study was undertaken to evaluate the safety of duct-to-mucosa procedure in our patients with pancreatoduodenectomy. Methods: We have performed pancreatojejunostomy in 14 consecutive patients using a duct-to-mucosa technique and the result was assessed. Results: No patients developed pancreato-jejunal leakage; however, 6 of 14 patients developed complications not related to operative techniques (wound infections; 3,jejunal fistula following removal of jejunal feeding tube; 1, renal dysfunction; 1, delayed gastric emptying; 1) which were managed conservatively. There were no postoperative deaths in the present series and the median postoperative hospital stay was 20.3 days. The follow-up period ranged from 1 to 12 months and all patients are surviving with good health during this period. Conclusion: Pancreatojejunostomy by duct-to-mucosal technique is a safe method of pancreatojejunostomy after pancreatoduodenecytomy.